Strategi Pedagang Dalam Praktik Jual Beli Cabai dengan Sistem Bibitan Perspektif Ekonomi Islam di Kecamatan Jangkar Kabupaten Situbondo - Zainul Anwar (Institut Agama Islam Negeri Jember, 2021)
Seedling System is the practice of buying and selling chili peppers between farmers and traders, which was previously preceded by the provision of chilli seeds from traders to farmers free of charge, giving these seeds by the trader as a strategy so that farmers, especially those who lack capital, can keep farming planting chilies and becoming a permanent supplier of chili to the trader. This study uses qualitative research with a case study approach. The results of the study showed that giving seedlings from traders to farmers including the bi syartin grant agreement, Ulama 'differed in their legal status, according to the Hanafi, Maliki, Hambali and Syafi'i sect (in qoul adharnya) saying the law was valid, while according to some Syafi sect. 'i (the opposite of qoul adhar) and some of the Hambali sect say that it is invalid, on the grounds that the grant agreement is a Tabarru contract' which is very contrary to compensation